James B Beard: The father of contemporary turfgrass science. Issue 1 (25th February 2021) - Stahnke, Gwen K.; Rieke, Paul E.; Cookingham, Pete O.; Shearman, Robert C.; Gaussoin, Roch E.; Kopec, David M.
Abstract: James B Beard (24 Sept. 1935 to 8 May 2018) can rightly be considered the "Father" of contemporary turfgrass science. During his career, he was known for setting a standard that provided the foundation for turfgrass science through his thorough approach to research, teaching, mentoring and communications. The books he published outlined a vision for an evolving scientific discipline. He trained and mentored >45 domestic and international doctoral and master students and numerous post‐doctoral trainees, who in turn continued to raise the quality of contemporary turfgrass science in the USA and internationally. He led the effort to change the name of Division C‐5 of the Crop Science Society of America (CSSA) from Turfgrass to Turfgrass Science, making C‐5 an important and a vital part of the society. His subsequent rigorous education and mentoring of others continued to strengthen the division. He recognized the importance of quality, peer‐reviewed science and the need for C‐5 to be represented on the Crop Science Journal (CSJ) Editorial Board to expedite this goal. His leadership and encouragement led to the creation of a C‐5 Technical Editor position on the CSJ Editorial Board in 2002. Beard provided the vision and worked with other leaders worldwide to develop the International Turfgrass Society (ITS) and the ITS Research Journal. The ITS and its leaders and members have been instrumental in enhancing turfgrass science internationally. Beard's leadership, along with others in turfgrass academia and industry, resulted in the USGA Turfgrass and Environmental Research Program that provides a competitive grant‐fund source for turfgrass research. Beard appreciated and vigorously studied history and contributions to turfgrass science by those who went before us. He leaves behind a legacy in science that deserves recognition and respect. It is our hope that this synopsis of Beard's career accomplishments will inspire present and future turfgrass scientists to follow in his footsteps.